STRATEGI PENCAPAIAN INDIKATOR PERILAKU KESEHATAN PADA INDEKS PEMBANGUNAN KESEHATAN MASYARAKAT (IPKM) DI KABUPATEN BONDOWOSO - Isa Ma’rufi (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
Public Health Development Index is a composite indicator that describes the progress of the health development in an area. The purpose of this research is to examine the strategy of achievement of health behavior indicators Public Health Development Index in Bondowoso. This type of research was descriptive, with variable parameters indicators of health behavior are behavior of smoking, hand-washing behavior correctly, using toilets for defecation, physical activity sufficiently, and brushing teeth properly. The analysis used SWOT analysis and Public Health Development Index in 2013. Value index of indicators for health behavior was 0,575. The highest proportion of value behavioral health is the proportion of hand washing correctly (74,2) and lowest proportion is physical activity sufficiently (71,4), with a value of the index parameter is the proportion of hand washing correctly is 0.140 and proportion of brushing teeth properly is 0.135. Health behavior index achievement strategies with the improvement of preventive and promotive activities in accordance with BOK until the basic health access is convenient to be realized. Keyword: health behavior, Public Health Development Index, the strategy of achievement